If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a + (23 + a) + (2a + -39) = 608 Remove parenthesis around (23 + a) a + 23 + a + (2a + -39) = 608 Reorder the terms: a + 23 + a + (-39 + 2a) = 608 Remove parenthesis around (-39 + 2a) a + 23 + a + -39 + 2a = 608 Reorder the terms: 23 + -39 + a + a + 2a = 608 Combine like terms: 23 + -39 = -16 -16 + a + a + 2a = 608 Combine like terms: a + a = 2a -16 + 2a + 2a = 608 Combine like terms: 2a + 2a = 4a -16 + 4a = 608 Solving -16 + 4a = 608 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + 4a = 608 + 16 Combine like terms: -16 + 16 = 0 0 + 4a = 608 + 16 4a = 608 + 16 Combine like terms: 608 + 16 = 624 4a = 624 Divide each side by '4'. a = 156 Simplifying a = 156
| a+(23+a)+(2a-39)=608 | | 54n=-16 | | 2-33=17 | | 3x^2-5x=x^2+2x-3 | | 3k-17=-4 | | 7y+4(y-5)=3(y+2)-5 | | 7+x=13+4x | | 2+3x-7= | | 9k+1=26 | | 3x=742 | | 13L+4+L=13+L | | 7c-8=20 | | 3x-12=5(x-3(7-2X)-7) | | x^2+6x+8=8 | | 3l+4+l=13+e | | 2a+8b+10a-6b= | | 8x+3=12+3x | | -(6y+5)-(-5y-7)=-3 | | 2x-44=2x | | .25r-0.25+0.25r=.5-0.25r | | ln(x)+ln(x-2)=5 | | h=-16t^2+112t+128 | | 5n-2=-2 | | ln(x)+ln(-2)=5 | | 5*n-2=-2 | | m+4=-16 | | -1+6x-4x=-1 | | -1+-6x-4x=-1 | | 2(x(x))=16 | | 5(-4q+3)=2q+3 | | 4(4x-2)=2(8x+4) | | 18+21.30-(-15)= |